Akibat Hukum Pemegang Komparisi Nominee Atas Beneficial Owner Saham Dalam Perseroan Terbatas - Ni Made Gina Anggreni; Nyoman Satyayudha Dananjaya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
The aims this article is to find out the norms violated against the nominee comparison in the nominee deed of the limited liability company establishment deed, to analyze the violated norms and principles related to the nominee comparison of beneficial owner shares in a limited liability company, and to analyze the legal consequences of the nominee comparison holder on the beneficial owner of the limited liability company shares. The research method used is normative legal research. The comparison of nominees in the deed of establishment of limited liability company violates several norms such as article 1320 of the Civil Code the objective requirements of a lawful cause, article 1338 of the Civil Code regarding good faith, ratification of the deed carried out by a notary in article 44 paragraph (1) of the Law on Notary Position-Changes, article 48 paragraph (1) and article 54 paragraph (4) of the Limited Liability Company Law, article 33 paragraph (1) of the Investment Law, article 2 of the Banking Law , money laundering, forgery of letters. The legal consequences for nominee comparison of the beneficial owner of shares not only cause the cancellation of the nominee agreement entered into by the nominee with the beneficial owner of the shares, but also appears to be very broad, namely the votes issued at the general meeting of shareholders, money laundering crimes, know your customer principle, inheritance process, taxes, actio pauliana in bankruptcy. Tujuan penulisan artikel jurnal ini untuk mengetahui pelanggaran norma terhadap komparisi nominee dalam akta nominee pada akta pendirian perseroan terbatas, untuk menganalisa norma dan prinsip yang dilanggar terkait adanya komparisi nominee atas beneficial owner saham pada perseroan terbatas, serta untuk menganalisa akibat hukum pemegang komparisi nominee atas beneficial owner saham perseroan terbatas. Adapun metode penelitian yang dipergunakan yakni penelitian hukum normatif. Komparisi nominee dalam akta pendirian perseroan terbatas melanggar beberapa norma seperti Pasal 1320 Kitab Undang-Undang Hukum Perdata yakni tidak memenuhi persyaratan objektif kausa yang halal, Pasal 1338 Kitab Undang-Undang Hukum Perdata mengenai itikad baik, pengesahan akta yang dilakukan oleh notaris pada Pasal 44 ayat (1) UU Jabatan Notaris-Perubahan, Pasal 48 ayat (1) dan Pasal 54 ayat (4) UU Perseroan Terbatas, Pasal 33 ayat (1) UU Penanaman Modal, Pasal 2 UU Perbankan, tindakan pencucian uang, pemalsuan surat. Akibat hukum terhadap komparisi nominee atas beneficial owner saham tidak hanya menimbulkan batalnya perjanjian nominee yang diadakan oleh pihak nominee dengan beneficial owner saham, namun nampak yang ditimbulkan sangat luas yakni terkait suara yang dikeluarkan saat rapat umum pemegang saham, tindak pidana pencucian uang, know your customer principle oleh bank, proses pewarisan, pajak, actio pauliana dalam kepailitan.